Earthquake Experience at Different Trimesters during Pregnancy Is Associated with Leukocyte Telomere Length and Long-term Health in Adulthood - Wang, Ran; An, Cuixia; Wang, Jincheng; Wang, Yumei; Song, Mei; Li, Na; Chen, Yanan; Sun, Feifei; Chen, Xingshi; Wang, Xueyi (Frontiers in Psychiatry, 2017)
Leukocyte telomere length (LTL) is a predictor of age-related diseases, cancer, and even early mortality. Prenatal stress experience has been suggested to associate with short LTL and an increased disease risk in adult life. The present study aimed to evaluate the 39-year effects of prenatal earthquake stress exposure on LTL and increased age-related disease risk in adulthood. Here, we compared the LTL in the subjects that were exposed to prenatal earthquake stress (PES) to healthy controls (CN) and evaluated whether stress exposure at different times during pregnancy is associated with a shorter LTL and long-term health conditions in adulthood. LTL was measured in 100 adults who experienced the 1976 7.8 Richter scale Thangshan earthquake of the Hebei province in utero and divided them into first, second and third trimester groups according to the exposure timing during pregnancy. A total of 80 healthy volunteers from Shijiazhuang of the Hebei province were also assessed for their LTL. The telomere-to-single copy gene (T/S) ratio of the PES group (0.78±0.06, p=0.04) showed a significantly lower LTL than the CN group (0.97±0.08). The results of the LTL analysis indicated that the subjects who experienced PES in the second (0.69±0.09, p=0.04) or third trimester (0.67±0.76, p=0.02) showed significantly shorter LTLs compared with those in the first trimester group (0.99±0.12). A fully adjusted regression model indicated the same conclusions. In addition, we found that systolic pressure (SBP;129.32±14.86mmHg, p=0.041), body mass index (BMI; 22.54±2.71, p=0.046) and low density lipoprotein (LDL; 3.09±0.98mmol/L, p=0.048) in the subjects with PES were significantly higher than those measurements in the CN subjects (SBP;122.06±10.55mmHg; BMI;20.24±2.13; LDL;2.91±0.76mmol/L), and there was a significant negative correlation between an increased adult hypertension risk and a shorter LTL.